Medieval saints and modern screens : divine visions as cinematic experience - Spencer-Hall, Alicia (Knowledge communities (Amsterdam, Netherlands) ;, 2018)
The thirteenth-century Latin hagiographic works known as the "Holy Women of Liège" corpus presents biographies filled with dramatic visions of God and intense physical unions with Christ. The texts that make up the collection demonstrate the problematic division of body and soul in the period and also reveal the potential of text to transmit visual experiences. This book explores those qualities of the texts using the latest developments in film theory, taking up such topics as the relationship of film to mortality, embodied spectatorship, celebrity studies, and digital environments